Age-related dynamics of predominant methanogenic archaea in the human gut microbiome - Mohammadzadeh, Rokhsareh; Mahnert, Alexander; Shinde, Tejus; Kumpitsch, Christina; Weinberger, Viktoria; Schmidt, Helena; Moissl-Eichinger, Christine (BMC microbiology, 2025)
The reciprocal relationship between aging and alterations in the gut microbiota is a subject of ongoing research. While the role of bacteria in the gut microbiome is well-documented, specific changes in the composition of methanogens during extreme aging and the impact of high methane production in general on health remain unclear. This study was designed to explore the association of predominant methanogenic archaea within the human gut and aging. Shotgun metagenomic data from the stool samples of young adults (n = 127, Age: 19-59 y), older adults (n = 86, Age: 60-99 y), and centenarians (n = 34, age: 100-109 years) were analyzed. Our findings reveal a compelling link between age and the prevalence of high methanogen phenotype, while overall archaeal diversity diminishes. Surprisingly, the archaeal composition of methanogens in the microbiome of centenarians appears more akin to that of younger adults, showing an increase in Methanobrevibacter smithii, rather than Candidatus Methanobrevibacter intestini. Remarkably, Ca. M. intestini emerged as a central player in the stability of the archaea-bacteria network in adults, paving the way for M. smithii in older adults and centenarians. Notably, centenarians exhibit a highly complex and stable network of these two methanogens with other bacteria. The mutual exclusion between Lachnospiraceae and these methanogens throughout all age groups suggests that these archaeal communities may compensate for the age-related drop in Lachnospiraceae by co-occurring with Oscillospiraceae. This study underscores the dynamics of archaeal microbiome in human physiology and aging. It highlights age-related shifts in methanogen composition, emphasizing the significance of both M. smithii and Ca. M. intestini and their partnership with butyrate-producing bacteria for potential enhanced health.